2011
DOI: 10.2147/ijn.s24552
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface charge on the potential toxicity of PLGA nanoparticles towards Calu-3 cells

Abstract: Background Because of the described hazards related to inhalation of manufactured nanoparticles, we investigated the lung toxicity of biodegradable poly (lactide-co-glycolide) (PLGA) nanoparticles displaying various surface properties on human bronchial Calu-3 cells. Methods Positively and negatively charged as well as neutral nanoparticles were tailored by coating their surface with chitosan, Poloxamer, or poly (vinyl alcohol), respectively. Nanoparticles were characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 56 publications
3
15
0
Order By: Relevance
“…Similarly, our alginate NPs showed a comparable cell viability (92% cell viability up to 250 µg/ml) as reported in previous studies (~90% viability at 50 µg/ml NP concentration, 24h incubation) using T47D breast cancer cells [42]. The higher cytocompatibility observed for PLGA-based NPs in our studies agrees with results by Mura et al[43], which showed more than 80% viability of Calu-3 cells incubated with PLGA and PLGA-CS NPs up to a concentration of 5 mg/ml for 24 h. These results indicate that all of our NP formulations are compatible with lung cells up to a high concentration of 1 mg/ml.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, our alginate NPs showed a comparable cell viability (92% cell viability up to 250 µg/ml) as reported in previous studies (~90% viability at 50 µg/ml NP concentration, 24h incubation) using T47D breast cancer cells [42]. The higher cytocompatibility observed for PLGA-based NPs in our studies agrees with results by Mura et al[43], which showed more than 80% viability of Calu-3 cells incubated with PLGA and PLGA-CS NPs up to a concentration of 5 mg/ml for 24 h. These results indicate that all of our NP formulations are compatible with lung cells up to a high concentration of 1 mg/ml.…”
Section: Discussionsupporting
confidence: 92%
“…These values are well below the previously established size cutoff of 100 nm diameter required for effective penetration through the brain parenchyma (30). In addition, all formulations were shown to have slightly negative surface potentials (ranging from −2 to −9 mV), which are well within the range of 0 to −15mV that we and others previously have shown to be optimal for preventing aggregation of particles, and for minimizing toxicity to cell membranes (31, 32). …”
Section: Resultssupporting
confidence: 72%
“…PLGA nanoparticles have been widely studied owing to their excellent biocompatibility and cytotoxicity towards various cell lines and have been approved by FDA and European Medicine Agency for many drug delivery applications 34 . Mura et al investigated the lung toxicity of PLGA nanoparticles displaying various surface chemistry and surface charge on human bronchial Calu-3 cells 35 . PLGA nanoparticles were tuned by coating with chitosan, Poloxamer, and poly (vinyl alcohol) for grafting positive and negative as well as neutral charges.…”
Section: Discussionmentioning
confidence: 99%